The Impact of Green Marketing on Consumer Purchasing Behaviour: The Moderating Effect of Social Influence - Feng, Lin (Transformations In Business & Economics, 2025)
Green marketing enables businesses to target consumers seeking eco-friendly products and services. The objective of this study was to examine the impact of green marketing on consumer behaviour and the moderating role of social influence. Drawing from the theory of planned behaviour and social influence theory, the study examined the moderating effects of normative, informational, and emotional social influences, as well as the mediating role of environmental consciousness. Using an online questionnaire, 927 valid responses were received from consumers across China. Partial least squares structural equation modelling (PLS-SEM) was done in Smart PLS 4. The results show that green marketing has a positive impact on consumer purchase decisions, with social influence having a statistically significant moderating effect. Environmental consciousness was found to mediate the relationship between green marketing and consumer behaviour. This study has both theoretical and practical implications by providing insights into the role of social influence on consumer purchasing behaviour in response to green marketing.